Decision Making in The Culture and Creative Industries Environment: Lessons from The Cultural Village - Chrisna T. Permana; Budi Harsanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Cultural village is an area-based development concept that engages with the culture and creative industries as well as tactical urbanism. Typically, a cultural village is situated in geographical areas that have traditionally had strong cultural themes and have the potential for socio-economic growth in the surrounding region. Decision-making in this environment differs from pure-profit sector decision-making. This study set out to draw lessons from the cultural village, especially in Global South, where the culturally-led consensus approach is used to reshape group decision-making processes. This study uses a systematic review method as a way to search, screen, analyze and synthesize knowledge from the academic database. The Scopus academic database is used for the search process. This paper concludes that the inclusion of culture into decision-making offers three stages of fundamental lessons for the community, which are flexibility, openness, and innovation. These three forms the foundation for the five main elements of decision-making in the cultural village, which include inclusive, participatory, collaborative, agreement-seeking, and cooperative. These findings suggest that the culturally-led consensus approach is a potential tool for policymakers to work with the community, especially to organize more bottom-up decision-making processes in traditional environments.